2017
DOI: 10.1039/c7mb00400a
|View full text |Cite
|
Sign up to set email alerts
|

mRNA–miRNA bipartite network reconstruction to predict prognostic module biomarkers in colorectal cancer stage differentiation

Abstract: Biomarker detection is one of the most important and challenging problems in cancer studies. Recently, non-coding RNA based biomarkers such as miRNA expression levels have been used for early diagnosis of many cancer types. In this study, a systems biology approach was used to detect novel miRNA based biomarkers for CRC diagnosis in early stages. The mRNA expression data from three CRC stages (Low-grade Intraepithelial Neoplasia (LIN), High-grade Intraepithelial Neoplasia (HIN) and Adenocarcinoma) were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 98 publications
0
24
1
1
Order By: Relevance
“…According to the study by Horvath and Dong (Horvath and Dong 2008), the signed weighted gene co-expression network (WGCN) was firstly constructed considering biweight midcorrelation (Song et al 2012) between the disease-specific DEGs (Huang et al 2017;Chen et al 2017;Motieghader et al 2017). Next, the modules were identified.…”
Section: Co-expression Network Construction and Disease-specific Modumentioning
confidence: 99%
“…According to the study by Horvath and Dong (Horvath and Dong 2008), the signed weighted gene co-expression network (WGCN) was firstly constructed considering biweight midcorrelation (Song et al 2012) between the disease-specific DEGs (Huang et al 2017;Chen et al 2017;Motieghader et al 2017). Next, the modules were identified.…”
Section: Co-expression Network Construction and Disease-specific Modumentioning
confidence: 99%
“…The miRNA set analysis using TAM tool 37 demonstrated that hsa-miR-20a-5p was significantly enriched in immune system, HIV latency, cell proliferation, angiogenesis and apoptosis. This makes it as an attractive candidate potentially involved in cell signaling and disease 1 . Thus, we searched hsa-miR-20a-5p in circRNA-miRNA-gene network in Circ2Disease.…”
Section: Resultsmentioning
confidence: 99%
“…Circular RNA (circRNA) is a type of RNA molecule which forms a covalently closed continuous loop by back-splicing or lariat 1 . Although circRNA was discovered decades ago, it was initially perceived as RNA splicing errors 2 .…”
Section: Introductionmentioning
confidence: 99%
“…iii) Graph and network theory-based researches: these approaches represents communication among the biological components through a graph or a network [24]. For this purpose, graph algorithms are applied to the generated system [25,26], and hidden interactions are detected [27]. Although these techniques are confronted with minimal validity challenges and produce significant results, they are not applicable to most drug repurposing cases because biological elements follow the hypergraph theory [28,29].…”
Section: -Backgroundmentioning
confidence: 99%